IMPLEMENTASI KEGIATAN EKSTRAKURIKULER BERBASIS KEAGAMAAN DALAM PEMBENTUKAN KARAKTER RELIGIUS PESERTA DIDIK DI SMK TRITECH INFORMATIKA MEDAN - Neliwati; Muhammad Syah Bagus; Diky Ananta Sembiring; Sandi Mahatir Harahap (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstrak. This research aims to investigate and analyze the implementation of religious-based extracurricular activities in shaping the religious character of students at SMK Tritech Informatika Medan. The primary focus of the study is to explore the impact of religious-based extracurricular activities on the formation of religious values, morals, and ethics among students. The research methodology involves participatory observation, interviews, and document analysis to gain in-depth insights into the implementation of extracurricular activities and their effects on students' religious character. The findings of this research are expected to provide additional insights into the effectiveness of religious-based extracurricular activities in developing the religious character of students within the context of SMK Tritech Informatika Medan. The implications of these findings may contribute positively to the design of extracurricular curricula in similar schools and provide valuable information for educators, parents, and other education stakeholders.